Verbal definitions of familiar objects in blind children reflect their peculiar perceptual experience. Issue 6 (13th September 2012) - Vinter, A.; Fernandes, V.; Orlandi, O.; Morgan, P.
Abstract Background The aim of the present study was to examine to what extent the verbal definitions of familiar objects produced by blind children reflect their peculiar perceptual experience and, in consequence, differ from those produced by sighted children. Methods Ninety‐six visually impaired children, aged between 6 and 14 years, and 32 age‐matched sighted children had to define 10 words denoting concrete animate or inanimate familiar objects. Results The blind children evoked the tactile and auditory characteristics of objects and expressed personal perceptual experiences in their definitions. The sighted children relied on visual perception, and produced more visually oriented verbalism. In contrast, no differences were observed between children in their propensity to include functional attributes in their verbal definitions. Conclusions The results are discussed in line with embodied views of cognition that postulate mandatory perceptuomotor processing of words during access to their meaning.